Strategic Management of Coconut Industry Investment and Regional Competitiveness - Nur Fitriayu Mandasari; Erwin; Haeruddin Hafid; Arlistria Mutmainnah; Nur Wahyuni Syahrir; Virda Evi Yanti Deril; Muhammad Ashdaq (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Coconut is a strategic commodity with high economic potential in West Sulawesi Province, yet its development and utilization remain suboptimal. This study aims to identify and strengthen the investment potential of coconut as a leading sector in the region. A participatory and systematic mapping approach was employed, combining secondary and primary data from planning documents, official statistics, field observations, and focus group discussions. Analytical methods included location quotient, shift share, and Klassen typology to assess the economic significance of coconut across regencies. The results indicate that coconut is a basic and growing commodity, particularly in Polewali Mandar Regency, with strong contributions to regional income. The development of coconut processing industries, especially coconut shell briquettes, shows high prospects due to abundant yet underutilized raw materials. Financial feasibility analysis confirms the viability of investment projects (NPV of IDR 24.94 billion, IRR 29%, Payback Period 3.9 years). This investment not only offers economic returns but also creates employment, increases farmers’ income, and promotes environmentally friendly energy. Strengthening synergies among government, business actors, and communities is recommended to support targeted and sustainable investment policies in coconut commodity development.